PENGARUH AKTIVITAS SUPERVISI KEPALA SEKOLAH TERHADAP PENINGKATAN PROFESIONALISME MENGAJAR GURU - Rijal Lubis, Alkausar Saragih (EDUCATE, 2022)
The school principal as a supervisor must be manifested in the ability of compiling, and implementing educational supervision programs, and utilizing the results. The ability to develop educational supervision programs must be realized in the preparation of class supervision programs, development of supervision programs for extra-curricular activities, development of library, laboratory and examination supervision programs. The aims of this research are as follows: (1) To obtain data and information about the supervision of school principals; (2) To obtain data and information on the professionalism of teachers at Perbaungan Dharma Utama High School; (3) To obtain data and information about the influence of the principal's supervision on teacher professionalism at SMA Dharma Utama Sukasari Perbaungan. The research hypothesis is: "There is an effect of the supervision of the principal on teacher professionalism at Dharma Utama Sukasari Perbaungan High School." This research was conducted at Darma Utama Sukasari Perbaungan High School with a total population of 25 people and a total sample of 25 people (total sample). above, a correlation value of 0.492 is obtained, while a correlation value in the correlation table (for N = 25 and a significant level of 5%) is obtained a value of 0.381. This means that the value of r(count) is 0.492 greater than the value of r(table) in the correlation table namely 0.381. Thus it means that the hypothesis formulated in this study can be accepted for truth, because the value of r(count) > the value of r(table) or 0.492 > 0.381.